Improving freeze thaw stability in dog rolls through selected meat binders : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Manawatu Campus, Palmerston North, New Zealand - Sei, Jerry Wakon (Massey University, 2020)
This Masters thesis was conducted to investigate the potential use of selected food gums, accepted and approved legislatively both within New Zealand and abroad, to improve the Freeze thaw stability of dog roll products. Dog rolls have evolved into popular pet food products marketed for the high-end user due to its high meat content and controlled use of additives. Given its popularity within New Zealand, it is currently only marketed locally due to having a short shelf life of up to three months at refrigerated storage. To increase market opportunities overseas, the shelf life of dog rolls must be increased, and freeze thaw stability must be maximised to allow export to market overseas under frozen storage. Improving the freeze thaw stability of dog rolls was carried out based on commercial considerations, customer acceptability and guided by a selection criterion to satisfy requirements of developing an acceptable commercial product within New Zealand and abroad. Product performance was based on analysing current commercial products under pilot scale performance using best performing functional ingredients and assessed using TPA hardness and measuring thaw drip loss after one freeze thaw cycle. Several hydrocolloids were considered potential candidates upon which only sodium alginate and iota carrageenan combined with the synergistic effect of xanthan gum and locust bean gum eventuated in an acceptable product when formulated with a chicken and pumpkin dog roll. The same combination of ingredients was tested using a beef and beetroot base product which did not achieve the same effect as in a chicken and pumpkin base product. The best performing combination of functional gums which improved the chicken-based dog rolls comprised kappa carrageenan (0.39 %), xanthan gum (0.07 %), LBG (0.22 %), CaCO₃ (0.04 %), and sodium alginate (0.23 %). Iota carrageenan performed similarly to sodium alginate when used in the same proportion in combination with the other gums and remained the favourable alternative ingredient over sodium alginate due to its lower cost while improving product performance for freeze thaw stability. Further optimisation for beef and beetroot dog roll products was recommended by assessing raw beef meat composition or using alternative vegetable filling.
The following Figures were removed for copyright reasons: 2-1 (=Batista de Vega et al., 2017 Fig 1) and 2-2 (Dea, Chapter 2, Conformational origins of polysaccharide solution and gel properties, in Industrial gums: Polysaccharides and their derivatives,1993 Fig 13).
Keywords: 400405 Food engineering